A method to assess the feasibility of implementing distributed Localised Manufacturing strategies in the food sector. (1st September 2020) - Gimenez-Escalante, Pedro; Garcia-Garcia, Guillermo; Rahimifard, Shahin
Abstract: Large-scale globalised food manufacturing systems have generated competitive advantages through economies of scale. However, these systems often show low environmental sustainability and resilience due to factors such as reliance on global food supply-chain actors and high emissions associated to transportation and storage. This article proposes increasing the sustainability of food production through a transition towards a 'Distributed Localised Manufacturing' (DLM) strategy. A novel assessment method is presented to evaluate the feasibility of DLM for different food products using nine distinctive metrics and a decision-support model to identify the most appropriate DLM system model for a specific scenario. An industrial case study is used to demonstrate the application of the novel assessment method. The results show that the DLM assessment method can accurately identify products that can benefit from the DLM strategy and potentially provide environmental and social benefits. In addition, the DLM assessment method demonstrated the ability to categorise key assessment criteria and support the selection of the most appropriate system model for a specific application. Finally, the method also provides guidelines to help to identify benefits, drivers and potential challenges that should be considered in future DLM implementations. In summary, this research presents a practical and powerful assessment method to support the implementation of a DLM strategy in the food-manufacturing sector in order to increase the long-term sustainability of food systems.